Histopathological evaluation of cesarean scar defect in women with cesarean scar syndrome. (21st December 2021) - Higuchi, Asuka; Tsuji, Shunichiro; Nobuta, Yuri; Nakamura, Akiko; Katsura, Daisuke; Amano, Tsukuru; Kimura, Fuminori; Tanimura, Satoshi; Murakami, Takashi
Abstract: Purpose: To explore the histopathological findings of cesarean scar defect (CSD) and the immunological component in women with cesarean scar syndrome (CSS). Methods: This retrospective study was conducted in a university hospital and a public hospital. A total of 63 patients with secondary infertility due to CSS who underwent laparoscopic resection of the CSD lesion were enrolled (CSS group), and 21 patients who underwent hysterectomy with a history of cesarean section were enrolled as control (non‐CSS group). We compared the differences in histopathological findings of CSD lesions by hematoxylin and eosin staining and immunohistochemistry for CD3, CD20, CD56, CD68, CD138, myeloperoxidase, and tryptase between the two groups. Results: The frequency of presence of endometrium on the CSD surface was significantly lower ( p = 0.0023) and that of adenomyosis was significantly higher ( p = 0.0195) in the CSS group than in the non‐CSS group. The number of CD3‐, CD20‐, CD68‐, and tryptase‐positive cells was significantly lower in the CSS group than in the non‐CSS group; however, the number of CD138‐positive cells was significantly higher in the CSS group ( p = 0.0042). Conclusions: This study suggested that the absence of endometrium, presence of adenomyosis, and chronic inflammation in CSD contributes to secondary infertility due to CSS.